RELIQIOUS CONCIOUSNES IN THE CONTEXT OF CONTEMPORARY SOCIAL PROCESSES - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article describes the current state of religious consciousness, it analyzes the impact of contemporary social processes.